The role of lncRNA in the pathogenesis of chronic obstructive pulmonary disease - Jing Xie; Yongkang Wu; Qing Tao; Hua Liu; Jingjing Wang; Chunwei Zhang; Yuanzhi Zhou; Chengyan Wei; Yan Chang; Yong Jin; Zhen Ding (Heliyon, 2023)
Chronic obstructive pulmonary disease (COPD) is characterized by progressive and irreversible airflow obstruction with abnormal lung function. Because its pathogenesis involves multiple aspects of oxidative stress, immunity and inflammation, apoptosis, airway and lung repair and destruction, the clinical approach to COPD treatment is not further updated. Therefore, it is crucial to discover a new means of COPD diagnosis and treatment. COPD etiology is associated with complex interactions between environmental and genetic determinants. Numerous genes are involved in the pathogenic process of this illness in research samples exposed to hazardous environmental conditions. Among them, Long non-coding RNAs (lncRNAs) have been reported to be involved in the molecular mechanisms of COPD development induced by different environmental exposures and genetic susceptibility encounters, and some potential lncRNA biomarkers have been identified as early diagnostic, disease course determination, and therapeutic targets for COPD. In this review, we summarize the expression profiles of the reported lncRNAs that have been reported in COPD studies related to environmental risk factors such as smoking and air pollution exposure and provided an overview of the roles of those lncRNAs in the pathogenesis of the disease.